What Factors Aaffect Continuous Usage Intention In Health Applications? - Roy William; Edastama, Primasatria (Jurnal Ekonomi, 2024)
The Covid-19 pandemic is proven to cause an acceleration of digitization in the health sector, as shown by the surge in the use of health applications. The transition to post-pandemic will certainly affect one's intention regarding the continuous use of these health applications. This study aims to determine the relationship between perceived usefulness and perceived ease of use on customer satisfaction as well as variables of health consciousness, EWOM, and Self efficacy in influencing continuous usage intention of health applications in Jabodetabek. This research was conducted using a survey method with an online questionnaire to 200 respondents. Data analysis using Structural Equation Modeling (SEM) method with SPSS and SmartPLS software. The results showed that perceived usefulness, perceived ease of use and customer satisfaction have a positive effect on customer satisfaction. In addition, the variables of health consciousness, E-WOM and Self efficacy were also found to have a positive effect on continuous usage intention of health applications. From a managerial perspective, it is hoped that a manager can design content and features in a health application that are tailored to user needs so as to increase the user's desire to continue using the application.